Systematic review of the multicultural aspect in a therapeutic relationship - P. C. Hermangild, Deborah Priya; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Therapeutic relationship is the connection or alliance developed between a client and their mental health professional. In order for the relationship to be successful and beneficial for the well-being of the client, several factors come into play to determine the strength of the therapeutic relationship. This article intends to focus on the multicultural aspect of the therapeutic relationship and will systematically review the literature that explains how culture plays a role in determining the direction and effectiveness of the relationship. The reviewer attempts to explore and analyse the various cultural factors that facilitate a strong and positive therapeutic relationship as well as the factors that fail to do so. Overall, it has been found that several multicultural factors that include race, ethnicity, religion and language affect the strength and efficacy of the therapeutic relationship as it differs from culture to culture. Ultimately, this calls for all mental health professionals to further develop their knowledge and skills as well as to be multiculturally competent so that they can be culturally sensitive towards the client and build a good and healthy therapeutic alliance that warrants a positive treatment outcome.